Dense and Green Building Typologies. Research, Policy and Practice Perspectives. - (:unkn) unknown (Springer, 2019)
In this book, leading architects and landscape architects provide their perspectives on the design of dense and green building types in high-density urban contexts that can support higher population densities, higher standards of environmental sustainability and enhanced liveability in future cities.
Keywords: Bebauung; Baudichte; Green Building; Gebäudetypologie; Nachhaltiges Bauen; Wohnumfeldgestaltung; Beispielsammlung